Panggung Depan Anggota DPRD Kota Bengkulu dalam Menjalankan Fungsi Legislasi - Eceh Trisna Ayuh; Elfahmi Lubis; Evi Hafizah (Jurnal Khabar: Komunikasi dan Penyiaran Islam, 2025)
DPRD (Regional People's Representative Council) is a legislative institution that has a legislative function. Through the legislative function, DPRD has the authority to form and create Regional Regulations. This makes the role of DPRD very important in the process of a Regional government. In addition, DPRD also acts as a channel for community aspirations, which means that its role in the legislative function should aim for community welfare. The purpose of this study is to determine the front stage of DPRD members of Bengkulu City in carrying out their legislative function. By using the perspective of action theory, this study aims to understand the motivation, interpretation, and choice of actions of DPRD members in the legislative process. This study is a qualitative descriptive study that will provide research results in the form of words, not numbers. The results of the study reveal that the front stage of DPRD members of Bengkulu City in carrying out their legislative function can be caused by various factors including an understanding of institutions, personal interests, and political dynamics. DPRD members of Bengkulu City generally interpret situations and choose actions based on personal and institutional interests, even certain individuals. The decision-making process in forming and creating regional regulations involves complex negotiations between various interested parties.